Voluntary or Coercive? The Transfer of The European Union Emissions Trading System (EU ETS) Policy by Indonesia - Ibnu Farrel Imam Rahardjo; Reza Triarda (Universitas Tribhuwana Tungga Dewi, 2026)
Indonesia’s rapid institutionalization of carbon markets makes the transfer of the EU ETS urgent to examine because adopting a mature model without comparable domestic capacity may widen implementation gaps. This article examines how the European Union Emissions Trading System (EU ETS) was transferred into Indonesia’s Carbon Economic Value framework under Presidential Regulation No. 98 of 2021. It focuses on the reasons for transfer, actors involved, policy elements transferred, and degree and nature of transfer. The study uses a qualitative single-case study design, relying on desk review of key regulations, government and EU ETS reports, and NDC documents, with thematic analysis guided by Dolowitz and Marsh’s policy transfer framework. The findings show that the transfer did not occur through direct copying or coercive imposition. Instead, it leaning toward voluntary lesson-drawing, with the degree best categorized as emulation. Indonesia adopted the core logic and instruments of EU ETS, including cap-and-trade, MRV, registry-based administration, and carbon market governance, while adjusting them to domestic legal structures, institutional capacity, and policy priorities. The article concludes that this adaptive transfer will be effective only if Indonesia strengthens institutional capacity, builds credible MRV systems, ensures emissions data integrity, and improves inter-agency coordination.Institusionalisasi pasar karbon yang berlangsung di Indonesia membuat transfer EU ETS penting untuk dikaji, karena adopsi model yang telah matang tanpa kapasitas domestik yang sebanding dapat memperlebar kesenjangan implementasi. Artikel ini membahas bagaimana European Union Emissions Trading System (EU ETS) ditransfer ke dalam kerangka Nilai Ekonomi Karbon Indonesia melalui Peraturan Presiden Nomor 98 Tahun 2021. Fokus kajian diarahkan pada alasan transfer, aktor yang terlibat, unsur kebijakan yang ditransfer, serta derajat dan sifat transfer tersebut. Penelitian ini menggunakan desain studi kasus tunggal kualitatif dengan desk review terhadap regulasi utama, laporan pemerintah dan EU ETS, serta dokumen NDC, yang dianalisis secara tematik berdasarkan kerangka policy transfer dari Dolowitz dan Marsh. Temuan menunjukkan bahwa transfer tersebut tidak berlangsung melalui penyalinan langsung maupun paksaan eksternal. Sebaliknya, transfer yang terjadi cenderung bersifat voluntary lesson-drawing, dengan derajat transfer yang paling tepat dikategorikan sebagai emulation. Indonesia mengadopsi logika dasar dan instrumen utama EU ETS, termasuk cap-and-trade, MRV, administrasi berbasis registri, dan tata kelola pasar karbon, sambil menyesuaikannya dengan struktur hukum, kapasitas kelembagaan, dan prioritas kebijakan domestik. Artikel ini menyimpulkan bahwa transfer adaptif ini hanya akan efektif jika Indonesia memperkuat kapasitas kelembagaan, membangun sistem MRV yang kredibel, menjamin integritas data emisi, dan meningkatkan koordinasi antar lembaga.